Arid Central Asian Data Base (ACADB) for surface brGDGT samples - Lucas Dugerdil; Sébastien Joannin; Odile Peyron; Shafag Bayramova; Xiaozhong Huang; Dilfuza Egamberdieva; Jakhongir Alimov; Bazartseren Boldgiv; Lilit Sahakyan; Guillemette Ménot (PANGAEA, 2025)
The dataset combine lipid biomarkers from surface samples, the sample physicochemical properties and bioclimate parameters. The branched glycerol dialkyl glycerol tetraethers (brGDGT) were analysed using a high performance liquid chromatography coupled to mass spectrometry. The isomers were differentiated using the newest chromatographic method in order to obtain the 5-, 6- and 7-methyls differential fractional abundances. The dataset gathers new surface sample from Arid Central Asia (ACA, n = 162 from an area extending from the Caucasus to Mongolia and China) and previously published surface samples from the ACA (n = 599, from the same area). This ACADB (n = 761) is also aggregated with 2709 surface samples all around the world (WDB) for comparison purpose. The majority of these other data were already available in Raberg et al., (2022), https://doi.org/10.1594/PANGAEA.940052. The database is composed of three different files: (1) the fractional abundances of the 21 available brGDGT including the 5-, 6- and 7-methyl isomers, (2) the actual climate parameters for each surface sample, and (3) the environmental and physicochemical properties of each surface sample including all the metadata for each sample site. The climate parameters are the Aridity Index (AI extracted from the CGIAR database, Trabucco and Zomer, 2018), the Mean Annual Air Temperature (MAAT in °C), the Mean Annual Precipitation (MAP in mm.yr-1) and seasonal parameters such as the Mean annual temperatures Above Freezing (MAF in °C), Mean Precipitation for Cold and Warm Quarter (MPCOQ and MPWAQ in mm.yr-1) and Mean Temperature for Cold and Warm Quarter (MTCOQ and MTWAQ in °C). These parameters were selected from the original publications when available and extracted from the worldclim 2.1 extrapolated climate database if not (Fick and Hijmans, 2017). The environmental parameters are the sample name, sample type (soil, lacustrine, riverine, peat, bone, marine and groundwater), country, latitude (°N), longitude (°E), pH, Dissolved Oxygen (DO in mg.L-1), salinity (in mg.L-1), the reference of the publication and the database (i.e. ACADB or WDB).